2017
DOI: 10.18632/oncotarget.15471
|View full text |Cite
|
Sign up to set email alerts
|

The PIAS3-Smurf2 sumoylation pathway suppresses breast cancer organoid invasiveness

Abstract: Tumor metastasis profoundly reduces the survival of breast cancer patients, but the mechanisms underlying breast cancer invasiveness and metastasis are incompletely understood. Here, we report that the E3 ubiquitin ligase Smurf2 acts in a sumoylation-dependent manner to suppress the invasive behavior of MDA-MB-231 human breast cancer cell-derived organoids. We also find that the SUMO E3 ligase PIAS3 inhibits the invasive growth of breast cancer cell-derived organoids. In mechanistic studies, PIAS3 maintains br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…In addition to its regulation on STAT3, PIAS3 exhibits anti-tumorigenic roles via other mechanisms, including regulating nuclear factor-κB, PI3K/AKT, and TGFβ pathways 11 , 14 , 25 , 37 , reducing the activity of transcription factors such as MITF, Oct4, and others 38 , 39 . As a SUMO (small ubiquitin-like modifier)-E3 ligase, the anti-tumor functions of PIAS3 are also associated with sumoylation enhancement and degradation of oncoproteins 40 42 , as well as a promoting regulation of p53 and ATR by inducing p53 sumoylation 43 45 . The complicated mechanisms of PIAS3 in tumorigenesis indicate that besides STAT3, other potential downstream pathways mediating the cancer-promotion of Smad6–PIAS3 axis in gliomas still need to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its regulation on STAT3, PIAS3 exhibits anti-tumorigenic roles via other mechanisms, including regulating nuclear factor-κB, PI3K/AKT, and TGFβ pathways 11 , 14 , 25 , 37 , reducing the activity of transcription factors such as MITF, Oct4, and others 38 , 39 . As a SUMO (small ubiquitin-like modifier)-E3 ligase, the anti-tumor functions of PIAS3 are also associated with sumoylation enhancement and degradation of oncoproteins 40 42 , as well as a promoting regulation of p53 and ATR by inducing p53 sumoylation 43 45 . The complicated mechanisms of PIAS3 in tumorigenesis indicate that besides STAT3, other potential downstream pathways mediating the cancer-promotion of Smad6–PIAS3 axis in gliomas still need to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…GRIN1 or NMDAR1 (N-Methyl-D-Aspartate Receptor Subunit NR1) was shown to be expressed in breast cancer specimens, but not in normal breast and to be involved in tumor growth [ 31 ], being thus, a potential oncogene. SMURF2 (SMAD specific E3 ubiquitin protein ligase 2) is a tumor suppressor involved in the maintenance of genomic stability and suppression of breast cancer cells invasiveness [ 32 , 33 ]. PIK3AP1 (phosphoinositide-3-kinase adaptor protein 1), also known as BCAP , is involved in the phosphatidylinositol 3-kinase (PI3K) pathway and genome wide association studies suggest that the PIK3AP1 gene region might be involved in breast cancer predisposition [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study showed that knock-down of Smurf2 increases the proportion of invasive MDA-MB-231 cell-derived organoids. This group also demonstrated that PIAS3-dependent sumoylation of Smurf2 is important in suppressing the invasive behavior of these cells ( 77 ).…”
Section: Regulatory Roles Of Smurfs In the Decisive Cellular Processementioning
confidence: 95%